Correlation Between Heart Disease Clinics Based on NYHA Classification and CTR on Thorax Photos at Ibnu Sina Hospital Makassar - Alwi, Sitti Rafiqah; Syahril, Erlin; Safitri, Asrini; Tahir, Akina Maulidhany; Pratiwi, Dwi (Jurnal Biologi Tropis, 2024)
Heart disease is caused by damaged heart muscle cells that pump blood throughout the body. The cause is due to a lack of oxygen carried by the blood to the blood vessels in the heart or because spasms in the heart muscle result in failure of the heart's function to pump blood. The heart cannot carry out its function properly, as many as 48% of Indonesians experience heart disease. To determine the level of heart disease, the New York Heart Association (NYHA) is used. Increasing NYHA in heart disease can result in an increase in heart size. To determine the correlation between clinical heart disease based on the NYHA classification and CTR results on chest x-rays. Total sampling through secondary data with certain criteria. NYHA 1 (P = 20.2), NYHA 2 (P = 33.3), NYHA 3 (P= 32.3), NYHA 4 (P= 14.1). The heart grade levels based on CTR examination results, no cardiomegaly (<50%) (p= 22.2), mild cardiomegaly (>50-55%) (p= 76.8), moderate cardiomegaly (56-60) (p=0 .0), severe cardiomegaly (>60%) (p=1.0) while symptoms of weakness (n = 57%), palpitations (n = 47%), no shortness of breath (n = 68%), no chest pain ( n = 50%). So there is a significant relationship between NYHA classification and CTR results on Thorax photos. In conclusion, there is a significant relationship between NYHA classification and CTR results on Thorax photos.